Heterologous Expression and Transglycosylation of Acarviosyltransferase - XUE Zhenglian, WANG Yuqing, LI Chuang, LI Dandan, ZHU Sibao, LI Xiangfei (Shipin Kexue)
In order to further investigate the structural properties and catalytic function of acarviosyltransferase (ATase), a key enzyme in the biosynthesis of acarbose, its gene (acbD) was cloned from Actinoplanes sp. SE50 genome and heterologously expressed in Escherichia coli. Bioinformatics analysis showed that the conserved domains of ATase, the expression product of acbD, were highly similar to those of cyclodextrin glycosyltransferase, which belongs to the glycoside hydrolase 13 (GH13) family, and ATase possessed a signal peptide and a transmembrane domain. After removal of the coding sequences in the signal peptide, the soluble expression level of acbD increased by 23.4 times as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The optimal catalytic temperature and pH for the recombinant ATase were 30 ℃ and 7.0, respectively. The substrate spectrum showed that the recombinant ATase had the highest catalytic activity toward D-salicin (82.85 U/mL), followed by that (63.75 U/mL) toward L-sorbose. This is the first finding that L-sorbose can serve as an excellent glycosyl donor for ATase. The above results lay the foundation for further clarifying the catalytic mechanism of ATase.